High-Resolution DNA Copy Number Profiling of Malignant Peripheral Nerve Sheath Tumors Using Targeted Microarray-Based Comparative Genomic Hybridization - Mantripragada, Kiran K.; Spurlock, Gillian; Kluwe, Lan; Chuzhanova, Nadia; Ferner, Rosalie E.; Frayling, Ian M.; Dumanski, Jan P.; Guha, Abhijit; Mautner, Victor; Upadhyaya, Meena (Clinical cancer research, 2008)
Purpose: Neurofibromatosis type 1 (NF1) is an autosomal dominant condition that predisposes to benign and malignant tumors. The lifetime risk of a malignant peripheral nerve sheath tumor (MPNST) in NF1 is ∼10%. These tumors have a poor survival rate and their molecular basis remains unclear. We report the first comprehensive investigation of DNA copy number across multitude of genes in NF1 tumors using high-resolution array comparative genomic hybridization (CGH), with the aim to identify molecular signatures that delineate malignant from benign NF1 tumors. Experimental Design: We constructed an exon-level resolution microarray encompassing 57 selected genes and profiled DNA from 35 MPNSTs, 16 plexiform, and 8 dermal neurofibromas. Bioinformatic analysis was done on array CGH data to identify concurrent aberrations in malignant tumors. Results: The array CGH profiles of MPNSTs and neurofibromas were markedly different. A number of MPNST-specific alterations were identified, including amplifications of ITGB4, PDGFRA, MET, TP73 , and HGF plus deletions in NF1, HMMR/RHAMM, MMP13, L1CAM2, p16INK4A/CDKN2A , and TP53 . Copy number changes of HMMR/RHAMM, MMP13, p16INK4A/CDKN2A , and ITGB4 were observed in 46%, 43%, 39%, and 32%, respectively of the malignant tumors, implicating these genes in MPNST pathogenesis. Concomitant amplifications of HGF, MET , and PDGFRA genes were also revealed in MPNSTs, suggesting the putative role of p70S6K pathway in NF1 tumor progression. Conclusions: This study highlights the potential of array CGH in identifying novel diagnostic markers for MPNSTs.